Parental involvement and barriers in transitional services for students with autism spectrum disorder in Saudi schools: a mixed-methods study - Ain, Ghaniah (Frontiers in Education, 2025)
IntroductionThis study explored the availability, quality, and challenges of transitional services for students with autism spectrum disorder (ASD) in Saudi Arabian middle and high schools, with a particular emphasis on parental perspectives.MethodsA mixed-methods approach was employed. Researchers first surveyed 301 parents regarding their awareness, involvement, and perceived barriers related to transition services. To deepen understanding, structured interviews were conducted with ten mothers from different regions of Saudi Arabia.ResultsMost parents (65.1%) expressed a desire to participate in transition planning, but only 37.2% reported consistent involvement. Parental recognition of the importance of transition planning was high (79.1%), and 74.4% supported their children’s right to appropriate services. However, only 30.2% strongly agreed they were aware of available services, while 37.2% disagreed, indicating a significant awareness gap. Key barriers identified included poor cooperation among families, schools, and community agencies, lack of standardized planning practices, insufficient policies, and inadequate financial and administrative support. Qualitative interviews revealed additional themes: parental confusion and anxiety about the future, exclusion from planning processes, lack of awareness about educational rights, and significant regional disparities in service provision. Parents described transitional services as fragmented, lacking long-term vision, and often excluding families from meaningful participation.DiscussionTransitional services for students with ASD in Saudi Arabia are inconsistently implemented and insufficiently designed to promote independence and life skills. The findings highlight an urgent need for policy reforms, greater parental engagement, and coordinated efforts among stakeholders to improve transitional outcomes for students with ASD. The abstract effectively presents quantitative findings from the survey data alongside qualitative themes from the interviews, providing a comprehensive overview of the research outcomes and their implications for policy and practice.